2015
DOI: 10.1093/mnras/stv616
|View full text |Cite
|
Sign up to set email alerts
|

A deep Chandra observation of the hot gaseous halo around a rare, extremely massive and relativistic jet launching spiral galaxy

Abstract: We present a deep Chandra observation of the extremely massive spiral galaxy 2MASX J23453268-0449256, the first X-ray observation of this very rare system which features the largest known relativistic jets from a spiral galaxy. We detect extended X-ray emission from the hot halo surrounding the galaxy, reaching out to 80 kpc in radius. The hot halo is elongated along the plane of the spiral galaxy, and one possibility is that the powerful relativistic jets have disrupted the hot halo gas located perpendicular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(69 citation statements)
references
References 40 publications
6
61
2
Order By: Relevance
“…By extension, our sample of five 'outlier AGN', might indicate that misalignment is rather commonplace as suggested by other authors by other means including from the angle of the jet (e.g. Clarke, Kinney & Pringle 1998;Nagar & Wilson 1999;Kinney et al 2000, although see also Walker, Bagchi & Fabian 2015 for the discovery of FRII jets in a massive spiral galaxy which appear aligned with their host) and from the inclination of the narrow line region (e.g. Fischer et al 2013).…”
Section: Discussionsupporting
confidence: 61%
“…By extension, our sample of five 'outlier AGN', might indicate that misalignment is rather commonplace as suggested by other authors by other means including from the angle of the jet (e.g. Clarke, Kinney & Pringle 1998;Nagar & Wilson 1999;Kinney et al 2000, although see also Walker, Bagchi & Fabian 2015 for the discovery of FRII jets in a massive spiral galaxy which appear aligned with their host) and from the inclination of the narrow line region (e.g. Fischer et al 2013).…”
Section: Discussionsupporting
confidence: 61%
“…Here we present an analysis of newly obtained, arcsecondresolution ALMA interferometry of CO(1−0) of the nearby, z = 0.0755, massive spiral galaxy 2MASSX J23453269−044925 (J2345−0449 hereafter) with a stellar mass of M stellar = 4 × 10 11 M and a radio power of P 1.4 GHz = 2.5 × 10 24 W Hz −1 at 1.4 GHz (Bagchi et al 2014;Walker et al 2015). The galaxy was first mentioned in the literature by Machalski et al (2007), and then further discussed by Bagchi et al (2014), who obtained low-frequency radio observations with the GMRT and optical longslit spectroscopy along the major and minor axis of the 35 large stellar disk.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear spectrum is at the same time that of a Low-Excitation Radio Galaxy (LERG), a Weak-Line Radio Galaxy (WERG Tadhunter et al 1998), and a LINER (Bagchi et al 2014), ruling out the presence of strong radiative feedback from a bolometrically bright AGN. Star formation is too weak to drive an outflow (Walker et al 2015). Walker et al (2015) showed with Chandra X-ray imaging that the galaxy is surrounded by a bright X-ray halo, potentially with cavities along the jet axis, which they attribute to hot gas heated by the radio source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshino et al 2009;Miller & Bregman 2013Hodges-Kluck et al 2016) and for external galaxies (e.g. O'Sullivan et al 2007;Anderson & Bregman 2011;Bogdán et al 2013Bogdán et al , 2015Walker et al 2015;Anderson et al 2016). These observations have the potential to constrain the dynamics of the coronae in addition to their temperature and density profiles: for example, measuring the Doppler shifts of the OVII absorption lines toward an ensemble of AGNs, Hodges-Kluck et al (2016) ruled out a stationary halo and suggested that the hot gas contains an amount of angular momentum comparable to that in the stellar disc of the Galaxy.…”
Section: Introductionmentioning
confidence: 99%